2016
DOI: 10.1002/chem.201602425
|View full text |Cite
|
Sign up to set email alerts
|

N−H‐Type Excited‐State Proton Transfer in Compounds Possessing a Seven‐Membered‐Ring Intramolecular Hydrogen Bond

Abstract: A series of compounds containing 5-(2-aminobenzylidene)-2,3-dimethyl-3,5-dihydro-4H-imidazol-4-one (o-ABDI) as the core chromophore with a seven-membered-ring N-H-type intramolecular hydrogen bond have been synthesized and characterized. The acidity of the N-H proton and thus the hydrogen-bond strength can be fine-tuned by replacing one of the amino hydrogen atoms by a substituent R, the acidity increasing with increasing electron-withdrawing strength of R, that is, in the order H Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
(22 reference statements)
2
25
0
Order By: Relevance
“…The excited‐state proton transfer (ESPT) reaction has been recognized as one of the most fundamental and significant processes in various photochemical and photophysical fields . It cannot be denied that ESPT reaction dynamics have been widely investigated, both experimentally and theoretically, by many groups since the first experimental observation of the excited‐state intramolecular proton transfer (ESIPT) phenomenon by Weller et al In particular, after the discovery of ESIPT phenomenon, many scientists investigated the proton transfer dynamics, vibrational‐resolved spectroscopy, elementary photophysics, and femtosecond ESIPT compounds . In fact, the ESIPT exhibits a variety of potential applications in many fields, such as fluorescence sensors, white light‐emitting materials, biological probes, ultraviolet photostabilizers, organic optoelectronic devices, etc …”
Section: Introductionmentioning
confidence: 99%
“…The excited‐state proton transfer (ESPT) reaction has been recognized as one of the most fundamental and significant processes in various photochemical and photophysical fields . It cannot be denied that ESPT reaction dynamics have been widely investigated, both experimentally and theoretically, by many groups since the first experimental observation of the excited‐state intramolecular proton transfer (ESIPT) phenomenon by Weller et al In particular, after the discovery of ESIPT phenomenon, many scientists investigated the proton transfer dynamics, vibrational‐resolved spectroscopy, elementary photophysics, and femtosecond ESIPT compounds . In fact, the ESIPT exhibits a variety of potential applications in many fields, such as fluorescence sensors, white light‐emitting materials, biological probes, ultraviolet photostabilizers, organic optoelectronic devices, etc …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Chen et al . confirmed that the stronger H‐bond led to more favorable ESIPT thermally after researching a great deal of N‐H seven‐membered‐ring H‐bonded molecules.…”
Section: Introductionmentioning
confidence: 72%
“…Thus far, this reaction appears to be used mainly to produce a range of 5-ethylidene-4-imidazolones. [46][47][48][49] There are two different pathways this reaction can be implemented to produce 5-ethylidene-4-imidazolones; both are shown in Scheme 15. In method A, the more popular method, the imidazol-4-one ring is formed from a terminal azidoimide.…”
Section: Scheme 5 Domino Synthesis Of Imidazoquinazolinonesmentioning
confidence: 99%